STRUKTUR BIAYA PANEN CENGKEH DI DESA KANEYAN KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Regina Simbar; Esry O.H. Laoh; Welson M. Wangke; Ellen G. Tangkere (COCOS, 2014)
ABSTRACTRegina Simbar. Cost Structure of Cloves Harvesting In Kaneyan Village Tareran sub District South Minahasa regency under the guidance of H. O. Esry Laoh as a Chairman , Welson M. Wangke , and Ellen G. Tangkere as Members.The objective of this research is to determine the amount of costs incurred by the farmer at the time of clove harvest in Kaneyan village Tareran sub District, South Minahasa Regency. The research was conducted for five months from May to September 2014. The data used in the study were primary data and secondary data. Primary data collection were conducted by interview using a questionnaire, while secondary data are taken from the related government agencies. method of sampling is done with stratified random sampling method based on the amount of production with a total sample of 20 farmers clove into three strata. stratum I with a total production of < 250 kg , 250-500 kg stratum II and stratum III with total production of â‰¥ 500 kg . obtained in this study using descriptive analysis. The research result showed that the cost of harvesting was Rp. 40352.47 / kg and the average production was 468,3Kg . Cost clove harvest every strata is stratum I Rp . 38009.2 / Kg Stratum II Rp . 39 046 / Kg Stratum III Rp . 41337.7 / Kg .The harvesting cost in Kaneyan village clove harvest was relatively affordable and provide income for the farmers who harvest of cloves.